Peningkatan Pengetahuan Keselamatan dan Keamanan Konstruksi Rumah Tinggal di Kelurahan Karang Joang, Kota Balikpapan - Anggriani, Indira; Sukmara, Riyan Benny; Ariyaningsih, Ariyaningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
In the context of residential development, safety and security in construction are essential components of the lifestyle of individuals. The geographical condition of Balikpapan, which is susceptible to natural disasters such as landslides, floods, and fires, presents additional obstacles to the provision of safe and secure housing infrastructure. An example of this is the landslide disaster that happened in Karang Joang Village in 2021, which was caused by a lack of awareness regarding the safety and security of residential construction. The resulting damage to numerous houses in the village was significant. This paper tries to examine the practical implementation of construction safety standards in residential homes, including the use of safe building techniques and appropriate materials, through community service activities. This program provided the community with a more comprehensive understanding of disaster risk management and enhanced their ability to take proactive and reactive measures in the event of an emergency. The results of the questionnaire distribution shows that there was a significant difference in the level of community knowledge. In terms of construction design knowledge, more than 50% (from 3 people to 13 people) of residents answered that they already knew the safe construction design after listening to the community service presentation. The same result also occurred in the knowledge of methods, more than 50% (from 3 people to 11 people) of respondents have known the right construction method for their area after attending this community service presentation.